Nursing Students’ Practicum Readiness Using Virtual Learning Reality: A Pre-Experimental One Group Study - Farah Huwaida Qurrota Aini; Restuning Widiasih; Hesti Platini (Journal of Nursing Care, 2023)
Technology can be utilized in various fields, with no exception of nursing education in which virtual reality is used as an educational tool. However, the use of virtual reality as a learning media for nursing is still limited, especially as an introductory tool to practicum sessions. This study aimed to give a description on the use of virtual reality as a learning media towards the readiness of students in Faculty of Nursing, Universitas Padjadjaran. A pre-experimental one-group post-test only design was used. A total of 68 nursing students participated and completed a virtual reality suctioning simulation for 20 minutes. The data were analysed using a descriptive analysis consisting scores of minimums, maximums, mean, and standard deviation. The means and standard deviation for practicum readiness were 16.84 and 6.899 respectively. The minimum score acquired in total was 6 out of a possible correct answer of 45, with the maximum score acquired being 34. Based on the result, virtual reality as a learning media has effects on practicum readiness. Further studies should take the implementation of a comparison group and the number of opportunities for participants to do the simulation procedure into consideration so that practicum readiness is more comprehensively described